2018
DOI: 10.31235/osf.io/cg3j9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immigrant Health Trajectories in Historical Context: Insights From European Immigrant Childhood Mortality in 1910

Abstract: Recent studies of immigrant health have focused on an apparent paradox in which some new immigrants arrive healthier than expected but exhibit poorer health outcomes with duration of residence. Although a variety of explanations have been put forth for this epidemiological pattern, questions remain about the socio-historical generalizability of the empirical findings and accompanying theoretical explanations. By examining childhood mortality patterns of European immigrants to the United States in the early 20t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…Contrary to con tem po rary research that has fre quently found an immi grant mor tal ity advan tage, this study found higher mor tal ity among the for eignborn White pop u la tion in the early and mid dle parts of the twen ti eth cen tury. This is con sis tent with other stud ies that have found higher rates of child mor tal ity and over all mor tal ity for immi grants in the early 1900s (Bakhtiari 2018;Dribe et al 2020;Lieberson 1980;Preston and Haines 1991).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Contrary to con tem po rary research that has fre quently found an immi grant mor tal ity advan tage, this study found higher mor tal ity among the for eignborn White pop u la tion in the early and mid dle parts of the twen ti eth cen tury. This is con sis tent with other stud ies that have found higher rates of child mor tal ity and over all mor tal ity for immi grants in the early 1900s (Bakhtiari 2018;Dribe et al 2020;Lieberson 1980;Preston and Haines 1991).…”
Section: Discussionsupporting
confidence: 89%
“…Mortality dif fer ences for the 1-4 age cat e gory are more in line with age and time trends, and the higher for eignborn mor tal ity is con sis tent with find ings from research that has used cen sus records to esti mate child hood mor tal ity (Bakhtiari 2018;Dribe et al 2020;Haines and Preston 1997;Preston and Haines 1991). Relative gaps in mor tal ity rates were smallest in the mid dle of the age dis tri bu tion, between ages 25 and 54.…”
Section: Corrected Proofssupporting
confidence: 52%
See 3 more Smart Citations